Impact assessment of differential chlormequat chloride exposure on soil fungal community dynamics - Lin, Qiujun; Wu, Xianxin; Li, Lina; Peng, Tianshu; Zou, Xun; Li, Guang; Wang, Jianzhong; Guo, Chunjing (Frontiers in Microbiology, 2025)
IntroductionThis study investigated the dose-dependent effects of chlormequat chloride (CC) applications on soil fungal community structure and diversity in a peanut cultivation system.MethodsA controlled field experiment was conducted with four treatment regimes: control (CK, no CC application), low-dose (D, 45g active ingredient/ha), medium-dose (M, 75g a.i./ha), and high-dose (G, 225g a.i./ha). CC solutions were applied during critical growth phases (flowering and pod-setting stages). Rhizosphere soil samples were collected 30-days post-application for microbial analysis. Alpha diversity (e.g., Shannon index), beta diversity (community composition), and functional guild analysis of fungal communities were assessed.ResultsAlpha diversity assessments revealed significant concentration-dependent responses. The low-dose treatment (D) exhibited statistically higher Shannon diversity indices (p < 0.05) compared to other treatments. Beta diversity analysis indicated distinct community composition patterns under increasing CC concentrations, characterized notably by a substantial reduction in Ascomycota abundance (from 92.08% in CK to 25.84% in D). Basidiomycota displayed relative stability across treatments. Functional guild analysis identified significant shifts: pathogenic fungi like Neonectria spp. declined drastically (from 92.08% in CK to 25.84% under D treatment), whereas saprophytic fungi such as Plectosphaerella spp. proliferated markedly (28.68% in D; 22.82% in G vs. 2.26% in CK).DiscussionThese findings establish clear dose–response relationships between CC exposure levels and fungal community parameters. The relative stability of Basidiomycota suggests enhanced tolerance to CC stress compared to Ascomycota. The significant shifts observed in key functional guilds, particularly the decline in pathogens and proliferation of saprophytes, highlight the impact of CC application on soil fungal ecological functions.